1989
DOI: 10.1002/bdd.2510100307
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a specialized transport mechanism for the intestinal absorption of baclofen

Abstract: Absorption of the spasmolytic drug baclofen in three selected intestinal segments of living anaesthetized rats in situ, is shown to be a specialized transport mechanism obeying Michaelis-Menten kinetics. Equation parameters were calculated through different procedures, whose features are discussed. A computer method based on the integrated form of Michaelis-Menten equation which reproduces the entire time course of drug absorption from the data found in three intestinal perfusion series at different initial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…16 Fitting of Models to Data and Statistical Proceduress Absorption Rate MeasurementssAbsorption rate measurements were assessed both for baclofen and for taurine. In a previous paper 11 it was shown that baclofen absorption can be described as a specialized transport mechanism obeying Michaelis-Menten kinetics. Nevertheless, we used the classical first-order equation to measure baclofen intestinal absorption because it gives an accurate description of the absorption profiles within a limited time interval (i.e., from 0 to 30 min), with good correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Fitting of Models to Data and Statistical Proceduress Absorption Rate MeasurementssAbsorption rate measurements were assessed both for baclofen and for taurine. In a previous paper 11 it was shown that baclofen absorption can be described as a specialized transport mechanism obeying Michaelis-Menten kinetics. Nevertheless, we used the classical first-order equation to measure baclofen intestinal absorption because it gives an accurate description of the absorption profiles within a limited time interval (i.e., from 0 to 30 min), with good correlation coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…A rat gut in situ preparation, 10 modified as previously reported, [11][12][13] was used. Briefly, a midline incision was made and a fraction of the middle intestine of about 35 cm length (measured 30 cm from the pylorus) was cannulated.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose antipyrine was selected, since it is known to be only passively absorbed. 11 Therefore, solutions containing antipyrine 133 mM with and without verapamil 7 mM were perfused in the small intestine of the rat.…”
Section: Absorption Testsmentioning
confidence: 99%
“…These results are acceptable from a biopharmaceutical viewpoint. 12 The analytical technique used for antypirine was previously described 11 and validated.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The optimal exposure to R-baclofen for the treatment of spasticity or GERD may be a stable therapeutic plasma concentration. Because of limited absorption of baclofen in the large intestine, attempts to develop a sustained release formulation of the drug have not been successful (Merino et al, 1989).…”
mentioning
confidence: 99%